Impact of Covid-19 on Household Food Waste: The Case of Italy - Pappalardo, Gioacchino; Cerroni, Simone; Nayga, Rodolfo M.; Yang, Wei (Frontiers in Nutrition, 2020)
Covid-19 has significantly affected people’s food purchasing and consumption habits. Fears of disruptions in the food supply chain have caused an increase in the quantity and type of food bought by households. However, increases in food purchases could give rise to food waste with negative ramifications for the environment in terms of greenhouse emissions and groundwater pollution. To assess whether household food waste has changed during Covid-19 lockdown, we conducted a nationwide survey of household food purchasers in Italy. Although the amount of food purchases increased during the lockdown, our results show that food waste actually decreased as people mainly bought more non-perishable food. Interestingly, concerns about the impact that the pandemic could have on the waste management system and the desire not to add pressure to the waste management system are key drivers of decreased food waste in Italy during the pandemic. Our findings seem to suggest that Italian consumers are developing a new level of awareness about food waste with potential positive impacts on the environment in terms of reducing greenhouse gas emissions and groundwater pollution.